STRATEGY OF SPAСE DEBRIS TREATMENT - Pavliukh, Lesia; Syrotina, Irina; Todorovych, Olena; Kovalska, Viktoriia (Proceedings of National Aviation University (archive), 2018)
Purpose and Objectives of the Work. This scientific article is devoted to space debris management issues. The aim of this scientific investigation is assessment of the protection methods from the influence of space debris on the Earth. Methods of Research: ground-based measurements, space-based measurements, analysis of the protection strategies. Research Results. Providing of two protection strategies: shielding (space debris shields for both manned and unmanned spacecraft can be quite effective against small particles. Protection against particles 0.1-1 cm in size can be achieved by shielding spacecraft structures) and collision avoidance which is possible by reducing the amount of new debris created and, in the longer term, removing existing debris. Discussion. To improve the space environment we need to develop the complex approach, which, first of all, must include: 1) reducing creation of debris; 2) removing existing debris.